Soil Best Bets Compendium - Sommer, Rolf; Godiah, David; Braslow, Juliet (2016)
This Best Bets Compendium identifies and explains in detail practices, methods, technologies or initiatives that have the potential to maintain or increase the organic matter and fertility of soils. We, first of all, provide a very brief overview of each best bet, including its geographical cover and agro-ecosystem. The best bet is then evaluated against its associated Resource Requirements, Tradeoffs, Effectiveness, Risks, Framework conditions, Attractiveness and its Cross Cutting relevance as far as biodiversity, climate change adaptation, mitigation, gender, and participation is concerned. This includes a ranking of each best bet on a scale of -2 to +2; minus indicating a negative and plus a positive impact. We also highlight cases when farmers redesigned the best bet, as well as proven cases of success and additional literature sources. Resource requirements are further sub-divided into: Organic inputs; Inorganic inputs; Land, land tenure; Labour; Money, cash, loan; Time; Machinery, animal draught, other tools; Market demand; and Others. Each of these requirements is evaluated on a scale of 1 to 10 in terms of the probability that absence or excess of the required item/input jeopardizes the overall success of the best bet, Here, 1 means very little impact and 10 very high impact. Zero is used if the requirement does not apply. Users can also query the compendium, make comments, and – most importantly – add further best bets.